Pavilion of Federal Republic of Germany (Benjamin New Co., Ltd.)
Pavilion of Federal Republic of Germany - on Ile Notre-Dame, was designed by architects Frei Otto of Berlin and Rolf Gutbrod of Stuttgart. Its eight steel masts carry 100,000 square feet of translucent "sky" providing all-weather protection.